Frisbee Aerodynamics - Potts, J. R.; Crowther, W. J. (20th AIAA Applied Aerodynamics Conference & Exhibit 24 - 26 June 2002, St. Louis, Missouri, 2002)
The frisbee-like flying sports disc is a spin-stabilised axi-symmetric wing of quite remarkable design. The disc generates lift through forward velocity just like a conventional wing. From a backhand throw, spin is naturally given to the disc, which stabilises it in free-flight. This experimental investigation of a typical flying disc shape outlines wind-tunnel data including plots of aerodynamic loads verses angle of attack (AoA) which are compared to existing data in the literature, the effect of spin is also presented. The surface pressure distribution is presented as pressure profiles at the halfspan station and colour filled contour plots for both the upper and cavity surfaces. Surface and smoke wire flow visualisation techniques provide an explanation of flow structures which compare well with the pressure distributions. The asymmetries observed in the trailing vortices, for a spinning disc, allow an explanation of the aerodynamic generation of the rolling moment and side force. The free-flight of a flying disc is discussed based on the above.